1987
DOI: 10.1038/jcbfm.1987.132
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Cerebral Blood Flow in Subclinical Hepatic Encephalopathy and its Correlation with Plasma-Free Tryptophan

Abstract: Summary: Cerebral blood flow (CBF), measured by the noninvasive xenon-133 inhalation method, EEG, and plasma levels of ammonia (NH3) and free tryptophan were determined in 18 hospitalized cirrhotic patients af fected with subclinical hepatic encephalopathy, as diag nosed by the Kurtz test. CBF results were significantly lower (p < 0.001) in the patients' group as compared with a sex-and age-matched normal control popUlation, al though seven patients had values in the normal range. NH3 was increased only in six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…5 In the present study, the increase in cerebral perfusion during the MARS treatment may reflect the removal of albuminbound substances that also may be involved in the development of HE. 6,7 Ammonia appears to be implicated in the genesis of HE. 14,15 We showed that MARS is capable of decreasing arterial ammonia concentrations in patients with AOCLF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 In the present study, the increase in cerebral perfusion during the MARS treatment may reflect the removal of albuminbound substances that also may be involved in the development of HE. 6,7 Ammonia appears to be implicated in the genesis of HE. 14,15 We showed that MARS is capable of decreasing arterial ammonia concentrations in patients with AOCLF.…”
Section: Discussionmentioning
confidence: 99%
“…Albumin-bound substances, such as tryptophan and indolacetic acid, have been linked to both hepatic encephalopathy (HE) and a reduction in cerebral blood flow (CBF). 6,7 If the alleviation in HE seen in patients treated with MARS is caused by the removal of such substances, then CBF would be expected to increase during MARS treatment. 5,8 However, the effect of MARS on cerebral perfusion has not been evaluated.…”
mentioning
confidence: 99%
“…eral studies employing different methodologies have discussed global alterations in both cerebral blood flow (CBF) and metabolism in patients with HE (Fazekas et al, 1956;Baldy-Moulinier and Bo ries, 1977;Rodriguez et al, 1987;Ede et al, 1988;Almdal et al, 1989;Sari et al, 1990;Aggarwal et al, 1994), although technology capable of resolving regional alterations of cerebral hemodynamics has recently become available. Lockwood et al (1991) used positron emission tomography (PET) to exam ine regional alterations in CBF and metabolism, however, this study involved patients with only minimal encephalopathy.…”
mentioning
confidence: 99%
“…Group B: with florid NP-SLE (Table 2) Thirteen (76%) patients showed either diffuse (33,37,39,41) or focal (29,30,31,35,36,40,42,43,44) hypoperfusion. The four patients with a normal rCBF suffered from motor seizures (28 and 34: oculogyric crises), abnormal movements of the right arm (32), and cerebellar ataxia (38).…”
Section: Resultsmentioning
confidence: 99%